PENGARUH KONSENTRASI TAWAS TERHADAP PERTUMBUHAN BAKTERI GRAM POSITIF DAN NEGATIF - Ayu Fitria Helmiyati; Nurrahman . . (Universitas Muhammadiyah Semarang, 2010)
Bacteria growth with way of binner deviding, is one sel to part two. Time of generation is time by sel to require for to part, it kinds fate from species and condition of growth. The character of bacteries growth on food is heterotrof that need organic matters for it growth. The research was conducted in two phases, the first stage using the addition of Alum treatment 0,8%, 0,825%, 0,85%, 0,875%, 0,9%, 0,925%, 0,95% concentration and the second stage using 0%, 1%, 2%, 3%, 4% and 5% concentration. The result of research bacteri first stage is not indicate preferences gram positive bacteria or gram negative bacteria. The Second stage, the growth of gram positive bacteria inhibited at concentrations of 1% alum, whereas gram negative bacteria inhibited at concentrations of 2% alum. Statictic analyze with ANAVA indicate Alum concentrasion effect the growth of gram positive bacteria and gram negative bacteria. Key words = alum, bacterial growth